Bioavailability of phenolic compounds and antioxidant effects of wine pomace seasoning after oral administration in rats. (August 2016) - Del Pino-García, Raquel; Rivero-Pérez, María D.; González-SanJosé, María L.; Croft, Kevin D.; Muñiz, Pilar
Highlights: Healthy Wistar rats were supplemented a red wine pomace seasoning (RWPS). Bioavailability and acute and short-term beneficial effects were assessed. Acute RWPS-intake decreased oxidative stress and nitric oxide inactivation. 4-week RWPS-intake did not improve lipid peroxidation or nitric oxide production. Acute benefits of RWPS consumption may be transient in healthy subjects. Abstract: The bioavailability of phenolics contained in a powdered red wine pomace seasoning (RWPS) and its beneficial effects after acute and short-term supplementation were investigated. First, a single oral-dose of RWPS (300 mg/kg body weight) was administered to healthy Wistar rats (n = 6) and several phenolic acids were determined post-RWPS intake in plasma (0, 2 and 4 h) and urine (−3 to 0, 0–3 and 3–6 h). Higher prevention of lipid peroxidation (plasma and urinary F2 -isoprostanes) and improved nitric oxide bioavailability were observed in samples collected at 4 h and between 3 and 6 h ( p  <   0.05), suggesting an important antioxidant role of the metabolites generated by the action of colonic microbiota. In contrast, following 4 weeks of daily RWPS consumption, no significant differences were detected between supplemented and control groups for any of the biomarkers assessed, which indicates that acute beneficial effects of RWPS intake might be only transient under normal physiological conditions for this rat model.